2014
DOI: 10.1186/1756-0500-7-268
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of high-quality DNA from ethanol-preserved tropical plant tissues

Abstract: BackgroundProper conservation of plant samples, especially during remote field collection, is essential to assure quality of extracted DNA. Tropical plant species contain considerable amounts of secondary compounds, such as polysaccharides, phenols, and latex, which affect DNA quality during extraction. The suitability of ethanol (96% v/v) as a preservative solution prior to DNA extraction was evaluated using leaves of Jatropha curcas and other tropical species.ResultsTotal DNA extracted from leaf samples stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Of the preservation methods used, silica gel proved consistently reliable, while treatments involving heat or alcohol lead to recovery of less DNA, and of more degraded DNA. This is in line with previous reports (Staats et al, 2011;Särkinen et al, 2012;Bressan et al, 2014;Weiß et al, 2016). Contemporary field collections for molecular work are usually silica gel-dried, or less frequently, collected into high salt buffers or RNAlater; however, it is not always possible to work with recent plant material.…”
Section: Discussionsupporting
confidence: 82%
“…Of the preservation methods used, silica gel proved consistently reliable, while treatments involving heat or alcohol lead to recovery of less DNA, and of more degraded DNA. This is in line with previous reports (Staats et al, 2011;Särkinen et al, 2012;Bressan et al, 2014;Weiß et al, 2016). Contemporary field collections for molecular work are usually silica gel-dried, or less frequently, collected into high salt buffers or RNAlater; however, it is not always possible to work with recent plant material.…”
Section: Discussionsupporting
confidence: 82%
“…Specimens were imaged using an Olympus TG3 camera. For each sample, part of the apical tip of a frond was cleaned of epiphytes, cut into smaller fragments of approximately 0.5 cm × 0.5 cm, preserved in 100% molecular-grade ethanol (Bressan et al 2014), and stored in a -80°C freezer. In total, 25 out of the 44 samples collected were pressed as herbarium vouchers and deposited at the SINU Herbarium.…”
Section: Sampling Sites and Collectionmentioning
confidence: 99%
“…26 Ethanol was used in our protocol because a previous report indicated that highemolecular weight DNA could be extracted from cells fixed with it and yield DNA of equivalent quality to that retrieved from fresh and frozen tissue. 10 The need for the recovery of high-quality nucleic acids, such as DNA, in the current age of sequencing is 2-fold. High-quality DNA as a template for next-generation sequencing (NGS) technologies means low fragmentation and the availability of large numbers of templates for amplification.…”
Section: Discussionmentioning
confidence: 99%
“…This has proven to result in improved yields of nucleic acids at both the qualitative and quantitative levels. 10 In fact, molecular analysis from a variety of cytology formats (fluids, washes, aspirations, and cell blocks) have been documented to be reliable sources for molecular analysis. [11][12][13][14][15] Looking to further increase the value of cytology specimens, we have developed a microfluidic platform from which the cells in a cytologic specimen can be viewed for diagnostic purposes and later recovered for molecular analysis, all in the context of a formalin-free environment.…”
Section: Introductionmentioning
confidence: 99%